„Ich weiß, wem ich mein Depositum anvertraut habe“ (2 Tim 1,12) - Krauter, Stefan (Biblische Zeitschrift, 2024)
In commentaries on the Pastoral Epistles, views differ widely on the interpretation of παραθήκη in 2 Tim 1:12. This article briefly presents the idiomatic use of παρα(κατα)θήκη in Greek texts and classifies therein its use in the Pastoral Epistles. On this basis, the most common interpretations of 2 Tim 1:12 are critically evaluated. An alternative interpretation of 2 Tim 2:12 is discussed. This has been proposed only twice before: the first time in a somewhat remote place, the second time quite succinctly in a commentary. As a result, it has been either ignored or very quickly discarded in further discussion. This article will show that this is the most plausible reading of 2 Tim 1:12.